2007
DOI: 10.1177/147323000703500203
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte-depleted Blood Cardioplegia

Abstract: The effect of the depletion of leucocytes from cardioplegic and initial myocardial reperfusion blood on the inflammatory response and myocardial protection in patients with unstable angina undergoing cardiopulmonary bypass (CPB) was studied. Patients were allocated randomly to a leucocyte-depleted (LD) group or a control group. The LD group received continuous retrograde LD isothermic blood cardioplegia and the control group received isothermic blood cardioplegia. Blood samples were collected at seven time-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We finally identified 16 eligible studies on which to perform the meta-analysis. 1530 Table 1 lists the main characteristics of these studies. In total, our meta-analysis included data on 738 patients, 373 (50.5%) of whom underwent leukocyte filtration in the cardioplegia line and 365 (49.5%) with a control filter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We finally identified 16 eligible studies on which to perform the meta-analysis. 1530 Table 1 lists the main characteristics of these studies. In total, our meta-analysis included data on 738 patients, 373 (50.5%) of whom underwent leukocyte filtration in the cardioplegia line and 365 (49.5%) with a control filter.…”
Section: Resultsmentioning
confidence: 99%
“…Only one trial 15 had described a random component in the sequence generation process and was judged to have reported adequate allocation concealment for the other trials; 1630 the methods reported were judged to be unclear on the basis of random sequence generation and allocation concealment. Twelve trials 1519,21,22,2426,28,29 did not blind of participants and personnel; however, it was believed that the outcome was unlikely to be influenced by the lack of blinding. Five trials 15,20,22,23,26,27,30 were blinded to outcome assessment and it was unclear for the others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations